Impact of using thiocolchicoside during endoscopic ureteral calculi removal: A preliminary study. Issue 1 (2nd January 2016) - Akin, Yigit; Gulmez, Hakan; Ates, Mutlu; Ates, Erhan; Baykara, Mehmet
Abstract: Objective : To evaluate the effects of thiocolchicoside during endoscopic treatment of ureteral calculus.Material and methods : Between May 2014 and December 2014, 498 consecutive patients were enrolled. Exclusion criteria were operations under general anaesthesia, chancing laser lithotripter settings, and urinary tract infection. All patients were divided into three groups: Group 1 consisted of patients who were not administered thiocolchicoside, group 2 consisted of patients who were administered 5 mg thiocolchicoside, and group 3 consisted of patients who were administered 10 mg thiocolchicoside. Demographic, perioperative, and postoperative data were recorded. Complications were noted according to Clavien-Dindo classifications. A p value of p ≤ 0.05 was considered statistically significant.Results : A total of 427 patients (319 male and 108 female) with full data were investigated. Mean age was 43.3 ± 13.3 years. There were 157 patients in group 1, 141 patients in group 2, and 129 patients in group 3. Stone migration and operation time were significantly lower in groups 2 and 3 than in group 1 (respectively; p < 0.001, p = 0.03). However, usage of jj stents was significantly lower in group 3 than in the other groups ( p < 0.001).Conclusion : Stone migration can be decreased by using locally administered thiocolchicoside in irrigation solution during endoscopic treatment of ureteral calculus. Additional doses may decrease usage of jj stents and operation time.